Etnografia do cuidado: cartografia junto às pessoas em situação de rua em Novo Hamburgo - RS - Zwetsch, Binô Mauirá (2021)
This research aims to understand the different conceptions and practices of care for homeless people from their own perspective. The study was located in Novo Hamburgo / RS and was based on meetings with the interlocutors, held in public spaces and in public transport. Through the ethnographic and cartographic methods and the techniques of participant observation, floating observation, open interview and drawing, I sought to collect narratives and images, relating their itineraries and movements through the streets of the city to their notions of care, considering, especially their between people relationships and with public services specialized in serving the homeless population. The background reflection is located in the fields of Anthropology of Care, Urban and Visual Anthropology and is guided by the following analytical operators: care, selfcare, public policies and specialized services.